PENDEKATAN EKOSISTEM DALAM MEDIA PEMBELAJARAN SEBAGAI UPAYA KONTEKSTUALISASI HUBUNGAN INTERNASIONAL INDONESIA - Rachmat Panca Putera; Az Zahra Lihaya Sofa; Isnaini Titilas Nurjayanti; Ika Septiani Yuanda Putri (CV JK Riset Publishing Group, 2025)
Learning about Indonesia’s international relations at the elementary school level often remains abstract and decontextualized. This study aims to analyze the use of an ecosystem-based approach in instructional media as an effort to contextualize students’ understanding of Indonesia’s international relations. The research employed a qualitative descriptive-interpretative design. The participants were third-grade and sixth-grade students at SD Negeri 2 Siraman Pekalongan, Lampung Timur, with classroom teachers serving as key informants. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed thematically. The findings indicate that the ecosystem-based approach enables students to understand Indonesia’s international relations as systemic and interconnected relationships linked to their local social and environmental contexts. Third-grade students developed basic contextual understanding through ecosystem analogies, while sixth-grade students demonstrated more complex reasoning regarding interdependence and the impacts of international relations. This study concludes that an ecosystem-based approach has strong potential to enhance global literacy at the elementary level when supported by reflective and dialogic teacher mediation.